Combined Inhibition of Soluble Epoxide Hydrolase and Renin-Angiotensin System Exhibits Superior Renoprotection to Renin-Angiotensin System Blockade in 5/6 Nephrectomized Ren-2 Transgenic Hypertensive Rats with Established Chronic Kidney Disease - Čertíková Chábová, Věra; Kujal, Petr; Škaroupková, Petra; Varňourková, Zdeňka; Vacková, Šárka; Husková, Zuzana; Kikerlová, Soňa; Sadowski, Janusz; Kompanowska-Jezierska, Elzbieta; Baranowska, Iwona; Hwang, Sung Hee; Hammock, Bruce D; et al. (Kidney & blood pressure research, 2018)
BACKGROUND/AIMS: We found recently that increasing renal epoxyeicosatrienoic acids (EETs) levels by blocking soluble epoxide hydrolase (sEH), an enzyme responsible for EETs degradation, shows renoprotective actions and retards the progression of chronic kidney disease (CKD) in Ren-2 transgenic hypertensive rats (TGR) after 5/6 renal ablation (5/6 NX). This prompted us to examine if additional protection is provided when sEH inhibitor is added to the standard renin-angiotensin system (RAS) blockade, specifically in rats with established CKD. METHODS: For RAS blockade, an angiotensin-converting enzyme inhibitor along with an angiotensin II type receptor blocker was used. RAS blockade was compared to sEH inhibition added to the RAS blockade. Treatments were initiated 6 weeks after 5/6 NX in TGR and the follow-up period was 60 weeks. RESULTS: Combined RAS and sEH blockade exhibited additional positive impact on the rat survival rate, further reduced albuminuria, further reduced glomerular and tubulointerstitial injury, and attenuated the decline in creatinine clearance when compared to 5/6 NX TGR subjected to RAS blockade alone. These additional beneficial actions were associated with normalization of the intrarenal EETs deficient and a further reduction of urinary angiotensinogen excretion. CONCLUSION: This study provides evidence that addition of pharmacological inhibition of sEH to RAS blockade in 5/6 NX TGR enhances renoprotection and retards progression of CKD, notably, when applied at an advanced stage.
Keywords: epoxid hydrolasy; Albuminuria; hypertenze; Drug Therapy, Combination; míra přežití; Renin-angiotensin system; inhibitory ACE; krysa rodu Rattus; kombinovaná farmakoterapie; albuminurie; Survival Rate; Rats, Transgenic; Renal Insufficiency, Chronic; 5/6 nephrectomy; chronická renální insuficience; potkani transgenní; Hypertension; zvířata; Chronic kidney disease; Epoxyeicosatrienoic acids; Rats; Animals; nefrektomie; Angiotensin-Converting Enzyme Inhibitors; Soluble epoxide hydrolase; Nephrectomy; renin-angiotensin systém; Renin-Angiotensin System; Epoxide Hydrolases